Raspberry Pi Based Smart Surveillance Enhanced with Wi-Fi Tecnology - Murugan, C.; Balachandar, H.; Beston James, M.; Suriya Vekatesh, T. (International Journal of Engineering and Technology, 2018)
Nowadays, mobile devices are integrated with our everyday life. The security and remote surveillance system is increasingly prominent features on the mobile phone. The modern surveillance is integrated with many automation technologies.Â In this modern world crime has become ultramodern tools. In this current time a lot of incident occurs like robbery, stealing unwanted entrance happens, threatening abruptly robbery. So the does matters in this daily life. People always remain busy in their daily to daily work also wants to ensure their safety of their beloved things. To prevent such incidents, we are proposing a smart surveillance system enhanced with WI-FI technology. This work presents the monitoring and controlling of surveillance robot for safety enhanced with Wi-Fi technology. This system consists of webcam, PIR sensor smoke sensor and Raspberry PI. In this system, we are using PIR sensor to detect the motions or to trace out the intruders and smoke sensor to detect fire accidents. In above of any human movement or fire accident occurs, the system will activate the Web camera. The webcam will capture live data in the surroundings and transmitting the live video to the social network through WI-FI. Simultaneously, the alert message is send to the respective people. The system also consists of buzzer to alert the nearby people and sprays the chloroform liquid on the intruders.Â Â